Audio selfhypnosis through smartphone can reduce anxiety in pregnant women - Lisnawati Lisnawati; Rani Widiyanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Physical and psychological changes require adaptation to lifestyle adjustments with the pregnancy process that occurs. Problems in pregnancy can be a trigger for emotional reactions that are mild, severe to high levels. Some pregnant women have experienced nausea, vomiting, anxiety, or some have experienced pregnancy comfortably, without complaints. These different responses are influenced by factors: physical, perception, experience, education, emotion and family support. Of these several factors, thoughts and emotions dominate the response to pregnancy. Hypnosis is an effective communication method for incorporating new information or ideas into one's subconscious mind. Audio selfhypnosis in pregnancy, it is hoped that the discomfort in the form of anxiety felt by pregnant women due to direct and indirect factors can be minimized so that it can reduce the incidence of complications during pregnancy, childbirth and the postpartum period.Purpose: to find out the use of audio self-hypnosis has an effect on reducing discomfort in the form of anxiety in pregnant women.Method: Using quasi-experimental. The population is all pregnant women at the Majasem Health Center in 2021. Sampling is done by purposive sampling technique, namely 30 pregnant women who are divided into 3 classes of pregnant women. Respondents were first guided on how to do self-hypnosis, then were given audio self-hypnosis via a smartphone to practice at home once every day for 1 week. Anxiety was measured using a questionnaire before and after self-hypnosis. The analysis technique uses paired sample t test. Data is not normally distributed, bivariate analysis using Wilcoxon test.Results: The analysis showed that there was an effect of using audio self-hypnosis in reducing anxiety in pregnant women with a p value of 0.000.Conclusion: The use of self-hypnosis audio can reduce discomfort in the form of anxiety in pregnant women